Strategi Menghadapi Orang Munafik Menurut Alquran - Admizal, Iril (AL QUDS : Jurnal Studi Alquran dan Hadis, 2018)
In the Qur’an, the word nifaq with its various forms that contain the meaning of hypocrisy, called as many as 37 times, contained the meaning of holding, taking part in talking about something that in the religious view, the confession of one person is different from the others. This nature, can create a variety of problems, personal and community. Therefore, this paper is aimed at exploring Qur’anic verses that relate to the existence of hypocrites, especially about the strategy of confronting them through thematic commentary methods. This study found that the strategy of confronting the hypocrites according to the Qur’an are, (1) strengthening the loyalty of fellow Muslims, (2) rejecting them as close friends, (3) rejecting them as leaders, (4) jihad, (5) building awareness, 6) reproduce prayer